ORGANIZE SPORT TRAININGS AND INJURY REDUCTION MEASURES - Shovkiddin, Narziev; Dilrabo, Nizamova; Urkhiya, Turabekova; Mamura, Atabaeva; Zafar, Bozorov (International Journal of Psychosocial Rehabilitation, 2020)
This paper presents an overview of sport training organization, injures during the trainings, the main reasons of injures that adversely affect athlete’s activity , the analyses of weight of musculoskeletal system as well as offers recommendations and suggestions that should be given special attention.